2016
DOI: 10.1002/adsc.201600018
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Gold‐Catalyzed N‐ and O‐Functionalizations of Alkynes with Nitrones, Nitroso, Nitro and Nitroxy Species

Abstract: Nitrone and nitroso species are versatile compounds to react with alkenes or butadienes to access five-ands ix-membered nitroxy (N À O) containing heterocycles,t oo ffer further access to acyclic 1,3-and 1,4-aminoa lcohols after facile cleavage of the N À Ob onds.T he N-andO -functionalizationso f alkynes with nitroneso rn itroso species have been explored less wellt han the corresponding alkene reactions.I nr ecent decades,g old catalysts have enabled the electrophilic activation of alkynes with weak nucleoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(72 citation statements)
references
References 90 publications
0
72
0
Order By: Relevance
“…for C 22 H 23 S [M + H] + : 319.1515, found: 319.1506. Methyl-3,4,7,8-tetrahydro-2H-4a,8-methanodibenzo 9,138.8,136.4,133.5,133.3,125.9,125.2,124.4,124.4,124.3,123.3,120.9,120.3,119.8,110.0,46.9,42.9,35.9,35.7,34.7,29.2,26.6,17.9;HRMS (ESI) 1-(8-Methyl-3,4,7,8-tetrahydro-2H-4a,8-methanodibenzo 6,139.7,138.7,133.2,132.1,125.0,124.1,120.1,119.4,118.6,118.2,110.1,46.9,42.8,35.8,35.7,34.6,29.2,26.5,17.8;HRMS (ESI) Bromo-N-methyl-N-(8-methyl-3,4,7,8-tetrahydro-2H-4a,8 139.8,138.6,135.6,133.8,133.1,131.9,129.4,127.7,124.3,124.3,124.1,…”
Section: Representative Experimental Procedures For Gold Complexes C8 mentioning
confidence: 99%
See 2 more Smart Citations
“…for C 22 H 23 S [M + H] + : 319.1515, found: 319.1506. Methyl-3,4,7,8-tetrahydro-2H-4a,8-methanodibenzo 9,138.8,136.4,133.5,133.3,125.9,125.2,124.4,124.4,124.3,123.3,120.9,120.3,119.8,110.0,46.9,42.9,35.9,35.7,34.7,29.2,26.6,17.9;HRMS (ESI) 1-(8-Methyl-3,4,7,8-tetrahydro-2H-4a,8-methanodibenzo 6,139.7,138.7,133.2,132.1,125.0,124.1,120.1,119.4,118.6,118.2,110.1,46.9,42.8,35.8,35.7,34.6,29.2,26.5,17.8;HRMS (ESI) Bromo-N-methyl-N-(8-methyl-3,4,7,8-tetrahydro-2H-4a,8 139.8,138.6,135.6,133.8,133.1,131.9,129.4,127.7,124.3,124.3,124.1,…”
Section: Representative Experimental Procedures For Gold Complexes C8 mentioning
confidence: 99%
“…Homogeneous gold catalysis has become one of the most powerful synthetic tools to rapidly increase molecular complexity and diversity from readily accessible substrates in a single operation. [5][6][7][8][9][10][11] In carbocyclic and heterocyclic synthesis, for instance, it has provided a number of elegant routes to a variety of targets of potential synthetic value from 1,n-allenenes, -allenynes and -enynes (Scheme 1a). [6][7][8] Mechanistically, the reactions typically involve activation of the more electron-rich and accessible of the two π-bonds and functionalization by a remaining pendant group and/or second starting material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DOI: 10.1002/adsc.201801327 Nitrone is among the most important 1,3-dipolarophiles in cycloaddition chemistry and has been widely used to construct nitrogen-containing heterocycles with diverse electrophiles. [8] The cycloaddition of nitrones with methylenecyclopropanes is an extensively studied cycloaddition reaction that provides a direct approach to introducing the small cyclopropane ring into target molecules. [9] Cyclopropanes are prevalent in drug molecules and bioactive compounds, usually showing distinct bioactivity.…”
Section: Communicationsmentioning
confidence: 99%
“…Since the seminalr eport on the gold-catalyzed decomposition of ethyl diazoacetate and the subsequent trapping of the resulting gold-carbenoid species by Nolan, Díaz-Requejo, PØrez, and co-workers in 2005, [1] the number of synthetic applications based on the gold chemistry of diazo compounds has been growings teadily. [2] Among the synthetically usefult ransformations developed in this field, the reaction with arenes has attracted considerable interest as am eans to access functionalized benzene derivatives featuring an on-trivial substitution pattern.S omeo ft heseg old-catalyzeda rene CÀHb ond functionalizationsp roceeded with chemoselectivitiesp reviously unattainableu sing other metal complexes. In fact, in the abovementioned contribution, using ethyl diazoacetate as the carbene source,t he authors already reported that the formal insertion of the carbene unit into the aromatic CÀHb ond was the preferred path not only for benzene, but also for toluene and styrene (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%